Lift the Flap Questions & Answers About Art - Katie Daynes (London, United Kingdom Usborne Publishing Ltd, 2018)
What's the point of art? Why do artists draw themselves? Who were the Impressionists? Discover the answers to these questions and many more in this entertaining information book, containing over 60 flaps to lift. A great introduction to art for inquisitive young children, with links to specially selected websites for more information.
Keywords: PY UOI - How we express ourselves -- PY UOI - How we express ourselves; Art -- Art